Comparison of oral, vaginal and sublingual misoprostol for induction of labour in premature rupture of membranes after 34 weeks of gestation: a randomized controlled trial - Galidevara, Chandana; Chaturvedula, Latha; Habeebullah, Syed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Purpose of this study was to evaluate the efficacy and safety of different routes of administration of misoprostol - 50µg oral, 25µg vaginal and 50µg sublingual for induction of labour in women with premature rupture of membranes after 34 weeks of gestation. Methods: Women admitted to labour ward with premature rupture of membranes (PROM) after 34 weeks of gestation and requiring induction of labour were randomized into three groups. A total of 246 women participated in the study and were assigned to three groups to receive either 50µg oral misoprostol (n=80) or 25µg vaginal misoprostol(n=83) or 50µg sublingual misoprostol (n=83). The doses were repeated 4 hourly till active labour was established or up to a maximum of 4 doses. Patient factors, induction to delivery intervals, maternal side effects and fetal outcomes were noted. Results: The mean induction to active labour interval was not significantly different in the three groups (oral vs vaginal vs sublingual-7.52±4.8 vs 7.75±4.1 h vs 7.68±5.3 h; p=0.93). There was no significant difference in the induction to delivery time interval among the three misoprostol groups (oral vs vaginal vs sublingual - 10.9± 5.9 h vs 11.2±5.0 h vs 11.4±6.6 h; p= 0.88). Spontaneous vaginal delivery rate, instrumental delivery rate and lower segment ceasarean section rates were comparable among the three groups. The number of neonates with APGAR score <7 (low APGAR) at 1 minute of birth was highest in sublingual group and lowest in vaginal group which was statistically significant (oral vs vaginal vs sublingual, 16% vs 7.2% vs 20.5%; p= 0. 04). APGAR score <7 at 5 minutes was not significantly different among the three groups (oral vs vaginal vs sublingual, 4.8% vs 2.4% vs 7.2%; p=0.2). This implies that the need for immediate resuscitation was more in the sublingual group. Neonatal intensive care admission was least in the vaginal group although the difference was not statistically significant. Sublingual group had a higher rate of hyperstimulation and fetal heart rate abnormalities compared to oral and vaginal groups although these parameters did not reach statistical significance. Conclusions: Oral, vaginal and sublingual routes of administration of misoprostol are equally effective for labour induction in women with premature rupture of membranes after 34 weeks with sublingual route having slightly higher incidence of low APGAR scores at one minute for the neonate.